Certification Impact on Performance of PESH Teachers in State Junior High Schools in Paser Regency, East Kalimantan Province - Soeprayogie, Adithya; Hanani, Endang Sri; Priyono, Bambang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
This research is motivated by issuing the National Education System Law and the Lecturer Teacher Law regulating the teacher certification program, which allegedly impacts teacher performance to be more professional. This type of research is qualitative research to produce spoken or written words. Data collection by observation, interviews and documentation. Primary data were 10 certified Physical Education, Sport and Health (PESH) teachers, while secondary data resulted from observations, questionnaires, PTK, certificates and lesson plans. Naturalistic data analysis according to actual situations in the field. The results showed the performance of most 10 certified PESH teachers, with 4 competencies indicators still need improvement on 2 competencies, namely Pedagogic and Professional. Meanwhile, Personality and Social competences are in good category. Factors affecting performance based on normative commitment need to be improved, while the physical work environment conditions need improvement in school facilities, infrastructure and facilities. The welfare conditions of the 10 PESH teachers were categorized as quite prosperous financially. The conclusion of this research requires several inputs, including: PESH teachers should prepare lesson plans according to the conditions of each school. PESH teachers make scientific papers without waiting for promotion and archive properly. PESH teachers need to involve ICT during the learning process. PESH teachers remain in a lifelong learning attitude. The supervision carried out needs to involve an expert in PESH subject. The Regional Education Office should continue to hold training seminars to increase the knowledge of PESH teachers.